2019
DOI: 10.3390/nu11020473
|View full text |Cite
|
Sign up to set email alerts
|

Infant Cereals: Current Status, Challenges, and Future Opportunities for Whole Grains

Abstract: Infant cereals play an important role in the complementary feeding period. The aim of this study was to review existing research about the quantity, type, and degree of infant cereal processing, with a special focus on whole grain infant cereals. Accumulating evidence shows many benefits of whole grain consumption for human health. Likewise, consumers are frequently linking the term whole grains to healthiness and naturality, and sustainable food production becomes a more important aspect when choosing an infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 140 publications
(180 reference statements)
1
53
0
6
Order By: Relevance
“…A diet rich in fibre and bran improves constipation and it is recommended to children with symptoms [ 47 ]. Another important reason to increase the intake of wholegrain cereals is the higher content of vitamins and minerals [ 48 ]. The consequence of refining whole wheat, the main cereal in Spain, is the loss of large amounts of vitamin B, calcium, iron, potassium, magnesium, phosphorus, selenium and zinc [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diet rich in fibre and bran improves constipation and it is recommended to children with symptoms [ 47 ]. Another important reason to increase the intake of wholegrain cereals is the higher content of vitamins and minerals [ 48 ]. The consequence of refining whole wheat, the main cereal in Spain, is the loss of large amounts of vitamin B, calcium, iron, potassium, magnesium, phosphorus, selenium and zinc [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of refining whole wheat, the main cereal in Spain, is the loss of large amounts of vitamin B, calcium, iron, potassium, magnesium, phosphorus, selenium and zinc [ 45 ]. In fact, children and adolescents have some degree of deficit in folic acid, calcium, iron, magnesium and potassium [ 46 , 48 ]. Besides, the consumption of wholegrain foods may provide several benefits for human health.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of infant cereals can help promote oral skills and supply dietary fiber to thicken stool output and has also been shown to increase production of Bacteroides in the infantile gut. 56 As children grow, and adaptation occurs, HF can be considered, and, if not tolerated, AA formulas can be used. 7 At our institution, feedings begin as soon as possible after surgery, when bowel sounds are present, enteral tube drainage is no longer bilious, the abdomen is soft, and there is no vomiting.…”
Section: Types Of Enteral Feedingmentioning
confidence: 99%
“…Cereals are ranked the major susceptible crops to mycotoxin contamination, with maize being at the forefront [54]. Because of their excellent energy and nutritional sources, these crops serve as the main ingredient used in the production of foods for IYC [55]. Although studies have shown that the processing of food can lead to a reduction or degradation of mycotoxins, it is important to highlight that mycotoxins can be carried over to the final processed products, thus necessitating the need for good quality raw material [56][57][58].…”
Section: Cereal-based Productsmentioning
confidence: 99%